2013
DOI: 10.3109/08923973.2013.772195
|View full text |Cite
|
Sign up to set email alerts
|

Long-term bisphenol A exposure accelerates insulitis development in diabetes-prone NOD mice

Abstract: Exposure to the endocrine disruptor (ED) bisphenol A (BPA) used in polycarbonate plastic and epoxy resins appears ubiquitous since BPA can be found in over 90% of analyzed urine samples from all age groups. There is a parallel occurrence of increased prevalence in type 1 diabetes mellitus (T1DM) and an increased exposure to EDs the last decades. T1DM is caused by insulin deficiency due to autoimmune destruction of insulin producing pancreatic beta cells and has been suggested to be induced by various environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
60
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 85 publications
8
60
1
Order By: Relevance
“…Based on others experiments, it was decided to examine 100 µg/kg/day of BPA (Sigma Aldrich Company, Germany) (15)(16)(17) and according to our results in dose response experiment on insulin secretion of isolated islet, at in vitro condition, choose 4 nmol/kg/day of exendin-4. The solvent of BPA was ethyl alcohol with a final concentration of 0.1% and solvent of exendin-4 was distilled water.…”
Section: Animalmentioning
confidence: 99%
“…Based on others experiments, it was decided to examine 100 µg/kg/day of BPA (Sigma Aldrich Company, Germany) (15)(16)(17) and according to our results in dose response experiment on insulin secretion of isolated islet, at in vitro condition, choose 4 nmol/kg/day of exendin-4. The solvent of BPA was ethyl alcohol with a final concentration of 0.1% and solvent of exendin-4 was distilled water.…”
Section: Animalmentioning
confidence: 99%
“…The difference of about 700 million US$ is quite a small amount compared to the GDP of any country and hence the countries across the world could take this as an investment in global public health. Hypertension (Bodin et al, 2013; 189.2 382 2. Diabetes (Leranth et al, 2008;Song et al, 2012;Babu et al, 2013;Gong et al, 2013;Kim and Park, 2013 …”
Section: Resultsmentioning
confidence: 99%
“…In non-obese diabetic (NOD) mice, we have previously shown that BPA exposure can induce and increase the number of apoptotic cells in the pancreas (Bodin et al, 2014(Bodin et al, , 2013. These studies suggest that BPA act either by direct toxicity or via impaired clearance by tissue resident macrophages, as well as elicit systemic immune effects like altered cytokine expression.…”
Section: Discussionmentioning
confidence: 95%
“…Also with regard to immunerelated endpoints, epidemiological and experimental studies are inconsistent, but several authors have reported associations between urinary BPA concentrations in mother or child and the incidence of asthma and allergy (Donohue et al, 2013;Gascon et al, 2014;Kim et al, 2014;Spanier et al, 2012;Vaidya and Kulkarni, 2012). In experimental rodent studies, BPA has been reported to enhance allergic airway inflammation in mouse allergy models (Bauer et al, 2012;Midoro-Horiuti et al, 2010;Nakajima et al, 2012;O'Brien et al, 2014a;Petzold et al, 2014), impair non-allergic food tolerance induction (IgG) or certain mechanisms underlying oral food allergy tolerance (Menard et al, 2014b;Ohshima et al, 2007;Yamashita et al, 2003) and accelerate autoimmune diabetes development in non-obese diabetic (NOD) mice (Bodin et al, 2014(Bodin et al, , 2013. However, an impact of BPA on the development of food allergy, or tolerance tested in a food allergy model, have to our knowledge not been investigated.…”
Section: Introductionmentioning
confidence: 98%